Waqf Fund Management through Micro Waqf Bank Program in Indonesia - Danuwijaya, Fachry Ganiardi; M.Ag, Nurwahidin (UI Scholars Hub, 2022)
Waqf is a muamalah activity that has a very important economic and social role in Islamic history. Waqf is one of solutions to the problem of poverty and social inequality in society. The establishment of the Micro Waqf Bank initiated by the government together with the Financial Services Authority (OJK) has played an important role as one of the new Islamic microfinance institutions in financial inclusion in Indonesia. This paper will discuss how the management of waqf funds through the Islamic Waqf Bank program based on pesantren in efforts to alleviate poverty and social inequality which has become a chronic problem in Indonesia. The discussion in this paper uses the literature study method in which the writer's team looks for various sources of literature such as books, internet, journals and others. This paper confirms that the Micro Waqf Bank has an important role in the efforts to empower the economic community, especially for people who are around the boarding school but it is still necessary to make regular improvements both from the operational side of the Micro Waqf Bank and the alignment of the naming of the institution in order to avoid any misunderstanding among the community especially Muslims.